Surrogate based optimization of functionally graded plates using PSO and DE - Ribeiro, Leonardo Gonçalves (2020)
Optimization procedures are often employed in the design of functionally graded structures to achieve a superior efficiency. Thus, this paper aims at comparing the Particle Swarm Optimization and the Differential Evolution algorithms when applied to the optimization of FG plates. The optimization is carried out using the Isogeometric Analysis to evaluate the structural responses and Radial Basis Functions are used as a surrogate modeling technique to lower the computation cost. A Sequential Approximate Optimization approach is used to improve the surrogate model during the optimization process. The two optimization algorithms will also be compared in terms of accuracy and computational efficiency.